Cycle-based high-intensity sprint exercise elicits acute cognitive dysfunction in psychomotor and memory task performance - Dufner, Trevor J.; Moon, Jessica M.; Wells, Adam J. (Frontiers in Cognition, 2024)
Purpose To examine the impact of an acute high-intensity sprint exercise protocol (HISEP) for eliciting post-exercise cognitive dysfunction in psychomotor, attentional, executive, and memory tasks. Methods Twenty-four recreationally active adults (22 ± 4 yrs, 169.39 ± 10.07 cm, 75.80 ± 14.73 kg, 27.03 ± 9.55 BF%) performed a HISEP on a cycle ergometer. Average psychomotor reaction time (avgRT; Dynavision D2 Mode A & Mode B), mood (Profile of Mood States Questionnaire; POMS), and cognition (Automated Neuropsychological Assessment Metrics; ANAM) were assessed pre- (PRE), post- (POST) and 60-min post (60POST) HISEP. One-way repeated measures ANOVAs were used to assess changes across time. Results Fatigue (main effect: p < 0.001, ηp2 = 0.309) was significantly higher at POST compared to PRE (p = 0.007). Tension (main effect: p = 0.021, ηp2 = 0.154) was significantly lower at 60POST compared to PRE (p = 0.029). Mode A avgRT (main effect: p = 0.022, ηp2 = 0.153) was significantly slower at POST compared to PRE (p = 0.026). Throughput (TP) scores for ANAM code substitution-delayed (CSD) task (main effect: p < 0.001, ηp2 = 0.284) and matching to sample (M2S) tasks (main effect: p = 0.014, ηp2 = 0.169) were significantly lower at POST compared to PRE (p = 0.001 and p = 0.025, respectively), while mathematical processing (main effect: p = 0.002, ηp2 = 0.232) was significantly higher at 60POST compared to both PRE (p = 0.019) and POST (p = 0.005). No other significant changes in cognitive task performance were observed (p's > 0.05). Conclusions The HISEP is a feasible and time-effective fatiguing exercise stimulus capable of eliciting acute cognitive dysfunction in psychomotor and memory task performance. NCT05100589.